2021
DOI: 10.3390/jcm10163530
|View full text |Cite
|
Sign up to set email alerts
|

De Novo Cancer Incidence after Kidney Transplantation in South Korea from 2002 to 2017

Abstract: Advances in patient care and immunosuppressive drugs have improved graft survival, resulting in an increase in kidney transplantation (KT); however, persistent immunosuppression is thought to cause late occurrence of cancer. This population-based study consisted of a total of 14,842 patients whose data from the years 2002 to 2017 were collected from the National Health Information Database in South Korea. Malignancies occurred in 7.6% of the total KT patients. Prostate and thyroid cancers were the most common … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…In a population-based nationwide study conducted in South Korea, it was found that approximately 7% of all kidney transplant recipients developed cancer. The incidence of PTLDs, including Kaposi's sarcoma and non-Hodgkin lymphoma, was higher than in the general population when considering the standardized incidence ratio [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a population-based nationwide study conducted in South Korea, it was found that approximately 7% of all kidney transplant recipients developed cancer. The incidence of PTLDs, including Kaposi's sarcoma and non-Hodgkin lymphoma, was higher than in the general population when considering the standardized incidence ratio [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“… 3 4 The reported percentage of KT patients receiving post-transplant transfusion has ranged from 28.0% to 37.2% in Canada and France, 15 21 and 49.7% of KT recipients received RBC transfusion during the perioperative period in Korea. 19 When we excluded patients who received transfusions of two or more types of RBCs, 48.0% of 17,754 KT recipients received RBC transfusion during the perioperative period between 2002 and 2017.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, in order to reduce the risk of allosensitization, leuko-reduced RBCs are preferable for KT recipients 9 ; however, in practice, several additional types of RBC preparations including pRBCs, filtered RBCs, and washed RBCs have been transfused into Korean patients. 19 Of the 8,530 patients who received RBC transfusion, 74.9% received filtered RBCs, 19.7% received pRBCs, and 5.4% received washed RBCs. Among the 77 institutions included in this study, 64 and/or 27 respectively used pRBCs and/or washed RBCs ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations